The Relationship between Types of Intelligence and Study Profile Options - Lupu, Costică (American Journal of Education and Learning, 2017)
Intelligence is a domain that has always interested people throughout history. Psychologists have become aware of the fact that real progress may be achieved only through collaboration, by unifying existing results and conclusions about the nature, function and modes of expression of intelligent behaviour. The ideal expression of such a synthesis would be a combination of the research findings of Sternberg and Gardner. To achieve effective results, each approach should diversify and refine its methodology and tools. This paper highlights the existence of a relationship between the predominant type of intelligence and the choice of the study profile, an aspect that may be taken into account in career guidance and counselling. Based on applying a battery of tests that measure verbal and logical-mathematical intelligence to a number of 86 subjects, students in the first year at the Faculty of Letters and Faculty of Sciences, the study highlights the fact that subjects have maintained their profile in the transition from high-school to university studies and there are significant differences in terms of the average logical-mathematical intelligence levels between the students from the real and those from the human profile. There are relevant differences between the mean of logical-mathematical intelligence levels of the subjects from the real profile and of those from the human profile, which confirms that at the students from the real profile the logical-mathematical intelligence is predominant. In terms of verbal intelligence, there are no relevant differences between the subjects from the real and those from the human profile, but for the entire research group there are significant correlations between verbal intelligence and the word scrambling test results.